2018
DOI: 10.3126/bibechana.v16i0.21319
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the firing temperature effects on clay brick sample; Part-I: Mineralogical phase characterization

Abstract: Present research work was focused to investigate the firing temperature effects on mineralogical phase composition of nine clay bricks collected from the brick factory of Kathmandu valley using X-ray diffraction (XRD) patterns and Fourier transform infrared (FTIR) spectra analyses. Main mineralogical phases of quartz, feldspars, spinel, mullite and hematite in the brick specimens fired at different firing temperatures including muscovite type of mica mineral in the sun-dried brick specimen are identified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The durability assessment of different types of clay bricks is mainly based on their technical physico-sintering and mechanical properties. However, such technical properties of the archaeological clay brick samples of Kathmandu valley are not reported in scientific communities, although mineralogy of the archaeological bricks (Ghale et al 2018), fired clay bricks at different temperatures (Bohara et al 2018) and ceramic tiles (Buthathoki et al 2018a, 2018b) were recently reported by some of the present researchers in Nepal. It was reported that the mineralogical phases existed in the archaeological clay brick samples collected from Kathmandu valley were identified as quartz, feldspars, spinel, muscovite type of mica mineral and hematite, and such clay bricks were considered to be fired at 900-1000 °C for their production (Ghale et al 2018).…”
Section: Introduction and Objectivementioning
confidence: 69%
See 1 more Smart Citation
“…The durability assessment of different types of clay bricks is mainly based on their technical physico-sintering and mechanical properties. However, such technical properties of the archaeological clay brick samples of Kathmandu valley are not reported in scientific communities, although mineralogy of the archaeological bricks (Ghale et al 2018), fired clay bricks at different temperatures (Bohara et al 2018) and ceramic tiles (Buthathoki et al 2018a, 2018b) were recently reported by some of the present researchers in Nepal. It was reported that the mineralogical phases existed in the archaeological clay brick samples collected from Kathmandu valley were identified as quartz, feldspars, spinel, muscovite type of mica mineral and hematite, and such clay bricks were considered to be fired at 900-1000 °C for their production (Ghale et al 2018).…”
Section: Introduction and Objectivementioning
confidence: 69%
“…The mechanical property of the compressive strength of the seven ancient clay brick samples was estimated in accordance with ASTM standards (ASTM C1424-15 2015) using the RAM DIA 222-2 mm with maximum load of 2000 KN compression testing machine available at the Central Material Testing Laboratory, Department of Civil Engineering of Pulchowk Engineering Campus, Tribhuvan University, Lalitpur using equation (4) as given below. The details about the estimation of the compressive strength of the seven ancient brick samples were described elsewhere (Bohara et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In the past, a few researchers studied the geological genesis [25][26][27][28][29], mineralogical [30][31][32][33], physicosintering [34][35][36][37], and ceramics [38][39][40] properties of clay minerals/soils of Nepal. A detailed study about the properties of porcelain raw materials deposited in Pachamane (Shivapuri conservation area of Kathmandu district) and Daman (Makawanpur district) areas of Nepal was carried out since the 1990s [9,32,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The demand for brick is accelerating worldwide, mainly due to rapid urbanization and associated socio-economic development. Urbanization is increasing at an average rate of 6% per annum, driving the demand for bricks for housing commensurately [1]. More than 1.5 trillion bricks are produced globally each year.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies about characteristics of bricks have been done before [1,2,6,7,8,9], however, none of them have assessed the quality of brick with respect to all influencing factors together [1,9] which this study aims to address. Though, this case study was performed on the bricks produced in Kathmandu Valley, the result would be applicable to other places where similar conditions exist.…”
Section: Introductionmentioning
confidence: 99%